Financial Privacy and the Theory of High-Tech Government Surveillance - Peter P. Swire (Washington University Law Quarterly, 1999)
Part I invites the reader to consider the problems of identity theft, the problems of having government access to each book and web page that an individual has accessed, and the risks of having an authoritarian or totalitarian government being able to trace every financial transaction within its borders. Part II introduces the metaphor of data entering a “vault 600 feet down,” and uses that metaphor to understand the range of ways that data can “reach the surface,” or become accessible. Part III systematically examines the advantages of government access to financial transaction data. Part IV examines the possible harms from government access to financial data.
Keywords: Right of privacy; Financial services industry; Electronic surveillance; Phase 2 Plus (Company); Bank secrecy